PENERAPAN STRATEGI THINK TALK WRITE (TTW) UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN KESETIMBANGAN KELARUTAN DI KELAS XI MIA SMA NEGERI 14 PEKANBARU - Azwendra, Yosi; Rasmiwetti, Rasmiwetti; Erna, Maria (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Research was aimed to improve study result of student on solubility and result times solubility subject has been doing in class XI science SMAN 1 Pekanbaru. This research was a form of experiments research with design pretest-posttest. Sample of the research were student of class XI science 3 as experimental class and class XI science 4 as control class. The experimental class was applied TTW learning strategy while the control class using discussion method. Data were analized using t- test. Result from the data analysis showed t count > t table (2,39 > 1,68). It means TTW learning strategy can increase the student learning achievement on topic of solubility equilibrium in class XI science SMAN 14 Pekanbaru with category of increase learning achievment on topic of solubility equilibrium in class XI science is high category.Key Word: study results, problem based learning, solubility and result time solubility